Two new genera of tokoriro (Orthoptera: Rhaphidophoridae: Macropathinae) from Aotearoa New Zealand - Trewick, Steven A. (Zootaxa, 2024)
Two new genera and three new species of forest inhabiting Macropathinae (Orthoptera: Rhaphidophoridae) are described from Aotearoa New Zealand. Crux Trewick gen. nov. is described with two new species, Crux boudica sp. nov. from Rakiura Stewart Island and southwest South Island and Crux heggi sp. nov. from northwest South Island. The monotypic genus Occultastella Trewick gen. nov. is represented by Occultastella morgani sp. nov. from northwest South Island.